SS thinking and the Holocaust. - Mineau, Andre. (Value Inquiry Book Series, 2012)
SS ideology was the expression of an apparently philosophical self-containing system of thought, articulated around a systematic body of knowledge claiming to integrate humanity inside a global vision of Being. Using ontology and anthropology as foundations, SS thinking developed essentially in the field of ethics. It portrayed itself as a global approach to society and civilization, based on eugenics and ethnic cleansing. It accomplished the fusion of the modern biological paradigm with the cultural shock brought about by World War I and promoted total war for the sake of total health. And since institutional philosophy largely ignores SS theory and praxis, Holocaust memorial institutions may represent an alternative for the development of understanding and reflection. Within the context of Nazism, SS thinking did much to work out the theory for which the Holocaust would be the ultimate accomplishment. It intended to provide the Holocaust with legitimacy, from the viewpoints of ontology, anthropology, politics, and ethics, whence the importance of studying the theoretical framework that gave sense to the most terrible form of SS praxis.